2020
DOI: 10.3389/fninf.2020.574189
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Non-invasive Deep Brain Stimulator With Precise Positioning and Real-Time Monitoring of Bioimpedance

Abstract: Methods by which to achieve non-invasive deep brain stimulation via temporally interfering with electric fields have been proposed, but the precision of the positioning of the stimulation and the reliability and stability of the outputs require improvement. In this study, a temporally interfering electrical stimulator was developed based on a neuromodulation technique using the interference modulation waveform produced by several high-frequency electrical stimuli to treat neurodegenerative diseases. The device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In this study, we constructed ideal sphere models and individualized human head models and then performed finite element analysis of the electric field at different frequencies of tACS. We found that the electric field intensity in the brain increased with increasing stimulation frequency under the same current intensity which was consistent with the experimental result (Wang et al, 2020). By comparing the simulation results, we found that the electric field intensity of the layered skull model more obviously changed with the stimulation frequency than that of the single‐layer skull model.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we constructed ideal sphere models and individualized human head models and then performed finite element analysis of the electric field at different frequencies of tACS. We found that the electric field intensity in the brain increased with increasing stimulation frequency under the same current intensity which was consistent with the experimental result (Wang et al, 2020). By comparing the simulation results, we found that the electric field intensity of the layered skull model more obviously changed with the stimulation frequency than that of the single‐layer skull model.…”
Section: Discussionsupporting
confidence: 92%
“…However, at the intersection of the two currents, there would form an envelope at a low-frequency equal to the difference of the two high-frequency currents (e.g., 20 Hz), which can modulate deep brain areas like conventional tACS ( Figure 1 ) [ 4 , 5 ]. Although the results of subsequent animal studies [ 6 , 7 , 8 ], simulation studies [ 9 , 10 , 11 , 12 , 13 , 14 ] and human studies [ 15 , 16 ] supported the effectiveness of TI-tACS in stimulating brain areas in a selective manner, its safety in stimulating human brains is still unclear. It is necessary to verify the safety of TI-tACS before we apply TI-tACS to human participants and patients.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of lesion positioning therapy is that it can precisely localize drugs to the lesion and produce an enrichment effect, which can greatly improve drug efficacy and significantly reduce the side effects caused by treatment. [ 1 , 2 , 3 , 4 ] At present, lesion positioning treatment of various diseases has been achieved through the application of functional biological materials, such as hydrogel microspheres [ 5 ] and electrospinning. [ 6 ] However, the physical barrier of the physiological structure of some tissues or organs (such as intervertebral discs [ 7 ] and cartilage [ 8 ] ) greatly hinders the implementation of lesion positioning therapy.…”
Section: Introductionmentioning
confidence: 99%